Johann Heinrich Hottinger : Arabic and Islamic studies in the seventeenth century - Loop, Jan (Oxford-Warburg studies, 2013)
The Reformed Church historian and orientalist Johann Heinrich Hottinger (1620-1667) is a key figure in the history of Arabic and Islamic studies in early modern Europe. His life and his work have been almost completely neglected and there has never been a full-length study on Hottinger. This book presents a thorough documentation of Hottinger's Arabic and Islamic studies. Based on printed books and a great number of unpublished and hitherto unknown manuscripts, the book assesses his scholarship in the context of seventeenth-century oriental studies and confessional rivalries. The book contains a biographical account of Hottinger and inserts him into the Zurich tradition of oriental studies, which can be traced back to Theodor Bibliander and Konrad Pellikan in the sixteenth century. It gives an account of his years as a student of Jacobus Golius in Leiden, where Hottinger copied and collected an impressive number of Arabic manuscripts on which he later based his teaching and his publications. The book explores Hottinger's network in the Protestant Republic of Letters and it contains studies of his activities as a bibliographer of Arabic texts, as a teacher of the Arabic language, as a linguist who promoted a comparative approach to oriental languages, as a student of the history of Islam and as a Protestant who used his knowledge of Arabic and of Islam in the theological debates of the time.
Keywords: Hottinger, Johann Heinrich, : 1620-1667; 1600-luku; Arabists : Biography; Arabic philology; Civilization, Arab; Islamic civilization; arabistiikka; orientalistiikka; islamilainen kulttuuri; tutkijat; Arab countries : History